Controle multivariável de temperatura e umidade aplicado em incubadoras neonatais - Brito Neto, José de Oliveira (2010)
A functional prototype to reproduce the micro-climate found in neonate incubators, as well as control circuits of temperature and relative humidity were designed and implemented in this work. The prototype is composite for sensors (temperature and relative humidity), actuators (heating resistor and humidificator), elements for accessible adjustment to the user and electronic circuits for signals control and processing collected in the prototype. The control circuits have the function of receiving the sensors signals and to activate actuators aiming keep the greatnesses in compatible landings with the norm NBR IEC-60.601-2- 19/1999. The incubator also has an air circulation system, formed by a fan, with the purpose of making homogeneous the temperature and humidity inside the same, besides providing for the renewal of the air. The characteristic multivariable of this type of system makes it interesting from the standpoint of application of control techniques. Therefore, we studied techniques of classical control, as the PI Controller, and the parameters set by the controller of this modified method of Ziegler-Nichols and BLT method and then compared the results obtained by these methods. Overall, the BLT method was more efficient than the modified method Ziegler-Nichols, since it allows flexibility in the specification of system performance.